The Impact of Hopscotch Game towards the Growth of Kinesthetic Intelligence on 3-4 Year Old Children - Khusnul Laely; Dede Yudi (Department of Early childhood Education, 2018)
This research aims to understand the impact of traditional game hopscotch towards the growth of kinesthetic intelligence on children enrolled at PAUD ALIF Kalinegoro, Kecamatan Mertoyudan, Kabupaten Magelang. The research employs experimental research design with One Group Pre-Postest Design. The experiment is conducted to one group without comparison group by using initial and final measurement. The variables in this research include children within 3-4 age group, amounting to 15 children enrolled at PAUD ALIF Kecamatan Mertoyudan Kabupaten Magelang. The samples are acquired using Total Sampling technique. The method for data collection is by using observation sheet and work method. The data analysis technique used is Wilcoxon Signed Rank Test with the help of computer program SPSS for Windows version 19.00.The results find asymp.sig. column (2-tailed)/asymptotic significance for two-tailed test is 0,001. Since the studied case is one-tailed test, the acquired probability is 0.001 / 2 = 0.0005. Based on this data, the probability is that 0.05 (0.00050.05), in which Ho is rejected, or in other words, there is a difference of kinesthetic intelligence on the initial and final measurement after the implementation of learning activity through traditional game hopscotch.